Ustekinumab improves psoriasis‐related gene expression in noninvolved psoriatic skin without inhibition of the antimicrobial response. (25th April 2013) - Baerveldt, E.M.; Onderdijk, A.J.; Kurek, D.; Kant, M.; Florencia, E.F.; Ijpma, A.S.; van der Spek, P.J.; Bastiaans, J.; Jansen, P.A.; van Kilsdonk, J.W.J.; Laman, J.D.; Prens, E.P.
Summary: Background Ustekinumab is a fully human anti‐p40 monoclonal antibody which neutralizes interleukin (IL)‐12 and IL‐23, thereby interfering with T‐helper (Th)1/Th17 pathways and keratinocyte activation, and is highly effective in the treatment of psoriasis. During ustekinumab treatment, some of our patients noticed reduced koebnerization of noninvolved skin and less new plaque formation. Objectives To determine whether ustekinumab improves psoriasis‐related gene expression and tape‐strip responses in noninvolved skin. Methods Before and 4 weeks after ustekinumab treatment, noninvolved skin was tape‐stripped. After 5 h, biopsies were taken from untouched and tape‐stripped skin. The mRNA expression of psoriasis‐related markers such as NGF, GATA3 and IL‐22RA1, and several antimicrobial peptides (AMP) was quantified. Leucocyte counts and a broad range of inflammatory serum proteins were analysed to gain insight into the systemic alterations. Results Four weeks following a single ustekinumab injection, NGF showed a significant decrease, whereas GATA3 and IL‐22RA1 expression increased, indicative of reduced responsiveness to epidermal triggering. This was accompanied by an increase of the inflammation‐related serum proteins GPNMB, MST1 and TRADD. The baseline and tape‐strip‐induced mRNA expression of the AMP human β‐defensin‐2 (hBD‐2), S100A7 and LL‐37 remained unaltered. Clinically, after 4 weeks, eight out of 11 patients showed a 50% psoriasis area and severity index (PASI) improvement, which was accompanied by a significant reduction in serum hBD‐2 levels. No changes were noted in total leucocytes, C‐reactive protein and erythrocyte sedimentation rate. Conclusions These findings indicate that ustekinumab reduces psoriasis‐related gene expression in noninvolved psoriatic skin, making it more resistant to exogenous triggering, without disturbing its antimicrobial response. In parallel, ustekinumab modulates important circulating inflammation‐related proteins. Abstract : What's already known about this topic? Ustekinumab is an effective biologic for psoriasis. Psoriasis‐related gene expression levels in noninvolved psoriatic skin are elevated compared with healthy skin. What does this study add? Ustekinumab improves psoriasis‐related gene expression in noninvolved psoriatic skin. Ustekinumab alters expression of inflammation‐related proteins in serum. Induction of antimicrobial peptides by tape‐stripping is not inhibited by ustekinumab. A weakness in our study is the limited number of patients studied; however, there are consistent results.